Analisis Manajemen Risiko Sistem Pembelajaran Online Pada Perguruan Tinggi Menghadapi Pandemi Covid-19 - Yusyida Munsa Idah; Ronggo Agatha Prima (JURNAL REKAYASA INFORMASI, 2021)
The application of information technology to support a business process should be consistent with the goal to be achieved, for if it is not appropriate it would be risky especially if it was abused. Risk assessment measures are intended to identify the risk profile of information technology, which is then assessed for risk, and then respond to that risk so that there are no adverse effects that such risks can cause. The purpose of this study is to analyze the risk management of the college's online learning information system when facing the covid-19 pandemic with the title "College Education Risk Management Analysis Coping With The Covid-19 Pandemic (Case Study: Amikom Purwokerto University)". The study uses a method that begins with the data-collection activity of identifying assets and then conducting asset values calculations. If value is obtained, then threat identification and asset deficiencies are made, then conduct business impact analysis, and then next conduct risk level and one last count of risk value to identify asset levels. The results of risk analysis and recommendations for online learning systems at Amikom Purwokerto University are 7 possible risks with high criteria, 1 possible risks with medium levels, and 5 possible risks with low levels.